Internal browning control in ‘laetitia’ plums by modified atmosphere, management of ethylene and storage temperature Controle do escurecimento da polpa em ameixas ‘laetitia’ com a atmosfera modificada e o manejo do etileno e da temperatura de armazenamento - Melo J.C.* (2021)
© 2021, Sociedade Brasileira de Fruticultura. All rights reserved.– The objective of this study was to evaluate the effect of modified atmosphere (MA) and 1-methylcyclopropene (1-MCP) treatment on low storage temperature (1.5 °C) and 1-MCP treatment on high storage temperature (8.0 °C) on fruit quality of ‘Laetitia’ plums, mainly on internal browning. The treatments evaluated were 1.5 °C; 1-MCP (1.0 µL L-1) + 1.5 °C; MA + 1.5 °C; 1-MCP + MA + 1.5 °C; 8.0 °C; 1-MCP + 8.0 °C. Fruit were stored for 30 and 40 days, followed by three day of shelf life. For fruit stored at 1.5 °C, the treatment with 1-MCP associated to MA provided higher flesh firmness, less intense skin red color and reduced occurrence of internal browning in comparison to the fruit stored at 1.5 °C of the remaining treatments, for both periods of storage. In fruit not treated with 1-MCP and stored at 8.0 °C there was no occurrence of internal browning, despite of lower flesh firmness and more intense red color of the skin and flesh in comparison to the fruit stored at 1.5 °C. The treatment with 1-MCP in fruit stored at 8.0 °C delayed those changes of flesh firmness and red color of the skin and flesh assessed after 30 days of storage, followed by three days of shelf life. The MA, regardless of 1-MCP treatment, had fruit with higher production of acetaldehyde after 30 days of storage, and ethanol after 30 and 40 days of storage at 1.5oC. In fruit stored at 1.5 °C without MA, the treatment with 1-MCP reduced the production of ethyl acetate, acetaldehyde and ethanol. Fruit stored at 8.0 °C, regardless of 1-MCP treatment, had the lowest production of acetaldehyde and ethanol.